Estimulación Transcraneal de Corriente Directa en Parkinson: Revisión Sistemática - Vega, Diana Marcela Prieto; Costa, María Lúcia Gurgel da (Revista Neurociências, 2013)
Introduction. Determine if Transcranial Direct-Current Stimulation (tDCS) can improve skills and be a safe method that it can be used as a tool for therapeutic support in patients with Parkinson’s disease. Method. A literature search was conducted on studies, published between the years 2002 to 2012 in the databases PubMed, SciELO and Bireme, in English, Portuguese and Spanish languages. Results. Nineteen bibliographic references were found, of these, five filled the inclusion criteria, however, only three references had a score equal to or greater than 3, fulfilling the methodological quality criteria according to Jadad scale parameters. One of these three references obtained the highest methodological quality score. Conclusion. The results of this review suggest that tDCS use is a safe method that improves motor skills such as gait and agility of upper limbs movements and cognitive abilities such as working memory. Also, it suggests be an option to accompany traditional therapeutic procedures. However, further research is needed to understand the therapeutics scopes.